2012
DOI: 10.1152/jn.00091.2012
|View full text |Cite
|
Sign up to set email alerts
|

Membrane properties and electrogenesis in the distal axons of small dorsal root ganglion neurons in vitro

Abstract: Although it is generally thought that sensory transduction occurs at or close to peripheral nerve endings, with action potentials subsequently propagating along the axons of dorsal root ganglia (DRG) neurons toward the central nervous system, the small diameter of nociceptive axons and their endings have made it difficult to estimate their membrane properties and electrogenic characteristics. Even the resting potentials of nociceptive axons are unknown. In this study, we developed the capability to record dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 55 publications
3
44
0
Order By: Relevance
“…Our results show that human Na v 1.8 channels produce a large persistent current that contributes to determining the firing patterns of DRG neurons. Na v 1.8 is known to be present in the central portion of primary afferent axons in the dorsal horn (Amaya et al 2000), and functional Na v 1.8 channels are known to be present along the neurites of DRG neurons in vitro (Vasylyev and Waxman 2012). It has been demonstrated that in some presynaptic terminals persistent currents can modulate transmitter release (Engel and Jonas 2005;Huang and Trussell 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that human Na v 1.8 channels produce a large persistent current that contributes to determining the firing patterns of DRG neurons. Na v 1.8 is known to be present in the central portion of primary afferent axons in the dorsal horn (Amaya et al 2000), and functional Na v 1.8 channels are known to be present along the neurites of DRG neurons in vitro (Vasylyev and Waxman 2012). It has been demonstrated that in some presynaptic terminals persistent currents can modulate transmitter release (Engel and Jonas 2005;Huang and Trussell 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that high-frequency biphasic stimulation causes extracellular accumulation of potassium (Cattell and Gerard 1935) or constant depolarization of the axonal membrane (Tanner 1962) to induce the block. Although the patch-clamp technique has significantly increased our understanding of sodium and potassium channel properties of the axonal membrane (Catterall 2012; Jan and Jan 2012; Schwarz et al 1995; Vasylyev and Waxman 2012; Waxman 2012), it has not been used to investigate axonal responses to high-frequency (>5 kHz) biphasic stimulation leaving the above proposals unconfirmed.…”
Section: Introductionmentioning
confidence: 99%
“…The saphenous skin-nerve preparation and ex vivo somatosensory system models developed by Reeh 3 and Koerber and Woodbury, 4 respectively, as well as other models using extracellular recordings from nerve fibers [5][6][7] monitor axonal activity following activation of the terminals, in different conditions, but not the activity at the terminals themselves. Electrophysiological recordings and ion imaging from terminal axons provided essential information about Na þ currents, which underlie action potential generation [8][9][10] and terminal Ca 2þ signaling. 11,12 Nevertheless, spatial constraints of the electrophysiological method make it unsuitable for studying biophysical properties of signal propagation along the cylindrical terminal and distal axon.…”
Section: Introductionmentioning
confidence: 99%
“…To study transducer channel-and action potential-mediated changes in terminal ½Ca 2þ in , we optically recorded changes in terminal GCaMP6s fluorescent intensity at a sampling rate of 1000 fps. As it has been shown that the half width of the action potential recorded from the distal neurite of nociceptive neurons is ∼2.5 ms, 8 this sampling rate should be sufficient to detect Ca 2þ reflections of single action potentials. We achieved this using a 60× oil 1.4NA Plan Apo objective, in combination with a fast acquisition back-illuminated 80 × 80 pixel CCD camera (see Sec.…”
mentioning
confidence: 99%
See 1 more Smart Citation